PELAYANAN JAMINAN KESEHATAN PADA MASYARAKAT MISKIN di RSUD.SOEDARSO PONTIANAK - Ayu Permatasari E.01108139 (FISIP Universitas Tanjungpura, 2013)
This article is intended to find out the implementation of the service given to Public Health Security Card Holders in the Inpatient Ward for Lung Problems at Dr. Soedarso Hospital, Pontianak. The purpose of this article is to be able to see the quality of service of the medical personnel in providing health services to patients who are jamkesmas card holders, and to see the state of existing support facilities such as beds for inpatients that do not meet the standard especially in the third class for lung treatment. This is qualitative research. The results indicated that the conditions of service in the provincial hospital Dr. Soedarso Pontianak especially for Jamkesmas card holders generally are still not good due to the complaint from patients regarding the service provided. The medical personnel are considered less responsive in providing service. The facilities are not sufficient. The medical personnel should show a friendly attitude, empathy, providing services in a fair manner by not distinguishing patients’social status as well as providing the best facilities. Keywords: quality of service, responsiveness and hospital Facilities.